Entrepreneurial alertness in eustress complex environments: An experimental approach of the exploitation/exploration dilemma. (4th May 2020) - Aimar, Thierry; Bouhdaoui, Yassine; Mateu, Guillermo; Sutan, Angela
Abstract: Technological and organizational constraints hinder entrepreneurial ability in alertly selecting/exploiting new opportunities. This article aims at showing that the complexity of the environment shapes entrepreneurial alertness. We build an experiment to mimic the choice alertness process (a case of eustress) and measure alertness and its relations with opportunity appearances, entrepreneurial effort, and complexity of the production structure. We show that alertness increases with the selection of more opportunities, but not with the complexity of the environment itself. At the same time, the entrepreneurial effort rate reduces alertness significantly more when participants are in a complex environment.